Morphology controlling method for amorphous silica nanoparticles and jellyfish-like nanowires and their luminescence properties - Liu, Haitao (Sci Rep, 2016)
Uniform silica nanoparticles and jellyfish-like nanowires were synthesized by a chemical vapour deposition method on Si substrates treated without and with Ni(NO(3))(2), using silicon powder as the source material. Composition and structural characterization using field emission scanning electron microscopy, transmission electron microscopy, energy dispersive X-ray spectroscopy and fourier-transform infrared spectroscopy showed that the as-prepared products were silica nanoparticles and nanowires which have amorphous structures. The form of nanoparticles should be related to gas-phase nucleation procedure. The growth of the nanowires was in accordance with vapour-liquid-solid mechanism, followed by Ostwald ripening to form the jellyfish-like morphology. Photoluminescence and cathodoluminescence measurements showed that the silica products excited by different light sources show different luminescence properties. The emission spectra of both silica nanoparticles and nanowires are due to the neutral oxygen vacancies (≡Si-Si≡). The as-synthesized silica with controlled morphology can find potential applications in future nanodevices with tailorable photoelectric properties.